Postura cranocervical y posición del hueso hiodes en niños con oclusiones de clase I, II y III - Pérez-Osorio, Luis Javier; Páez-Mejía, Ana (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The craniocervical posture and hyoid bone position were cephalometrically evaluated in 23 children (13 girls and 10 boys) with occlusion class I(8), class II (8) and class III (7), in the age group of 6-13 years cephalometric radiographs were taken in natural head position ("mirror position") and centric occlusion. The findings reveal some statistically significant differences: the class 111group show more straight craniocem-cal posture than class I group, and thehyoid bone in more down ward position than class II patients.